Aplikasi Perhitungan Pemenuhan Gizi pada Orang Sakit Menggunakan Metode Harris Benedict - Herry Hermawan (Jurnal Informatika dan Multimedia, 2018)
The National Health System states that all efforts in health development in Indonesia are directed towards achieving a higher degree of health which enables people to live more productively both socially and economically. With the increasing socio-economic status, public health services, lifestyle changes, increasing life expectancy, then in Indonesia there is a shift in the pattern of disease. Efforts to improve health for sick people can be done by maintaining food intake and meeting nutritional needs for sick people. Fulfillment of nutrition for the sick is fulfilling the nutritional needs needed by the body, such as calories, carbohydrates, protein, and fat. To overcome this problem, it is necessary to have an application to speed up the process of calculating nutrition fulfillment for sick people. Application is the application of a system design to process data that uses the provisions of certain programming languages and also a computer program created to help and facilitate human work. In the calculation process the application is made using the Harris Benedict method. Where the Harris Benedict method is used to do calorie calculation needed by sick people based on height, weight, age, activity factor and gender. In its application, this application uses the Microsoft Visual Basic programming language, with a Microsoft Access database. The final result of this application is in the form of nutritional information and food advice for sick people.Kata Kunci—